2021
DOI: 10.3390/ma14092348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fabrication Technique on the Microgap of CAD/CAM Cobalt–Chrome and Zirconia Abutments on a Conical Connection Implant: An In Vitro Study

Abstract: The aim of this in vitro study was to investigate the microgaps at the implant–abutment interface when zirconia (Zr) and CAD/CAM or cast Co–Cr abutments were used. Methods: Sixty-four conical connection implants and their abutments were divided into four groups (Co–Cr (milled, laser-sintered and castable) and Zirconia (milled)). After chewing simulation (300,000 cycles, under 200 N loads at 2 Hz at a 30° angle) and thermocycling (10,000 cycles, 5 to 50 °C, dwelling time 55 s), the implant–abutment microgap was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 44 publications
1
24
0
1
Order By: Relevance
“…This study found some of these complications, but always in the hexagonal connection group. Additionally, as known from different studies, new technologies such as CAD/CAM and posterior milling or laser-sintered processing may offer better results in terms of adjustment of the prothesis and the implant [52][53][54]. In addition, milling and sintering offer smoother surfaces that would retain less microorganisms and induce fewer inflammatory reactions [55].…”
Section: Discussionmentioning
confidence: 99%
“…This study found some of these complications, but always in the hexagonal connection group. Additionally, as known from different studies, new technologies such as CAD/CAM and posterior milling or laser-sintered processing may offer better results in terms of adjustment of the prothesis and the implant [52][53][54]. In addition, milling and sintering offer smoother surfaces that would retain less microorganisms and induce fewer inflammatory reactions [55].…”
Section: Discussionmentioning
confidence: 99%
“…Different prosthetic materials have been recently proposed since precious alloys have been gradually relegated due to the increasing gold price and with the CAD‐CAM technology developments (Edelhoff et al, 2019; Limones et al, 2020). Currently Titanium, Cobalt‐Chrome (Co‐Cr), or Zirconia (Zr) are some of the commonly used materials options by clinicians and patients due their accessibility, competitive price, and good clinical characteristics (Lemos et al, 2019; Molinero‐Mourelle et al, 2021). Zirconia abutments have been a reliable alternative with clinical advantages regarding the soft tissue behavior especially in the anterior region (Fonseca et al, 2021; Naveau et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The integrity of implant–abutment interface plays an important role in long‐term success and can be affected by the material type, the fabrication technique, and the processing method quality (Koutouzis, 2019; Pereira et al, 2017). Considering the sealing capacity and implant‐abutment microleakage, most of the studies focused on implants or the materials for components, and in this respect, precious alloys and titanium abutments have been widely investigated, and although Co‐Cr abutments present favorable properties, their seal capacity with respect to their fabrication technique has not been extensively studied; the number of published studies is limited (Jo et al, 2014; Koutouzis, 2019; Molinero‐Mourelle et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the implant-abutment microgap magnitude is important for the long-term clinical success of dental implants. The CAD/CAM abutments presented smaller microgaps [ 124 ]; microgaps (1–9 µ) make the entrance of bacteria into the favourable niche inside the implant difficult. Taking into account causes of adverse events, the prosthetic restorations made using CAD/CAM are not free of defects, as reviewed by Skorulska [ 125 ].…”
Section: Resultsmentioning
confidence: 99%